2017
DOI: 10.1051/matecconf/201711601018
|View full text |Cite
|
Sign up to set email alerts
|

The role of chemical admixtures in the formation of the structure of cement stone

Abstract: Abstract. The influence of sulfates and carbonates of potassium and sodium on the character of the formation of the microstructure of cement stone was studied. The role of cations in the structure formation of cement stone is shown. The efficiency of chemical additives, hardening accelerators, was estimated from the ratio of the volumes of gel and capillary micropores. The ratio of gel and capillary pores allows to determine the efficiency coefficient of the action of chemical additives. It is shown that the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…An earlier study articulated that K + would improve concrete formation by increasing gel porosity and decreasing capillary porosity. 22 It was reported that K + could interact with the alumina and silica in cement to improve microscopic strength in the hardened concrete. 21 Decreasing the compressive strength with further increasing OKLB2 dosages could be explained by the increased repulsion force in the cement paste.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…An earlier study articulated that K + would improve concrete formation by increasing gel porosity and decreasing capillary porosity. 22 It was reported that K + could interact with the alumina and silica in cement to improve microscopic strength in the hardened concrete. 21 Decreasing the compressive strength with further increasing OKLB2 dosages could be explained by the increased repulsion force in the cement paste.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Carboxylate ions were reported to form complexes with calcium ions on the cement surface, and remaining unadsorbed samples in the solution could enhance the interaction with cement particles during the hydration period, improving the cement compression strength. , Another reason could be the presence of potassium ions in the sample. An earlier study articulated that K + would improve concrete formation by increasing gel porosity and decreasing capillary porosity . It was reported that K + could interact with the alumina and silica in cement to improve microscopic strength in the hardened concrete …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To improve physical and mechanical characteristics, the authors [17] modify binding substances by clay fillers. The electrolytes, especially in the form of the complex additive, provide an increase in the water impermeability [18] and strength [19] of cement composites. In [19], such an influence of potassium and sodium sulfates and carbonates is explained by the modification of the microstructure and porous structure.…”
Section: Analytical Review Of Literature Sourcesmentioning
confidence: 99%